Analysis and Survey of the Book 50 Key Concepts in Gender Studies from the Islamic - Persian Perspectives - Maryam Saneapour (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
This article scrutinies the book, entitled 50 Key Concepts in Gender Studies by  Pilcher, Jane, and Whelehan, Imelda. The book provides an authoritative account of gender studies – what it is and how it originated. The author of this article has chosen the book because in Iran, there are many questions about gender studies, so it is necessary to analyze its key concepts. Then the author inquires about some of the gender concepts in Islamic – Persian tradition.  Then she introduces ten principles for global dialogue including the Persian language is none gender; equality of rights for women and men, gender justice, unity of matter and mind, synergistic of male and female in family, gender and syberic world, axial unity in gender and sexual communications, the authenticity of mercy, caring and maternal ethics, none gender of management jobs, human unit criterion for gender and sexual assessment.